2022
DOI: 10.1242/jeb.243404
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin mediates stress-like effects on responses to non-nociceptive stimuli in the medicinal leech Hirudo verbana

Abstract: Noxious stimuli can elicit stress in animals that produce a variety of adaptations including changes in responses to nociceptive and non-nociceptive sensory input. One example is stress-induced analgesia that may be mediated, in part, by the endocannabinoid system. However, endocannabinoids can also have pro-nociceptive effects. In this study, the effects of electroshock, one experimental approach for producing acute stress, were examined on responses to non-nociceptive mechanical stimuli and nociceptive therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…A 25-gauge needle was used to deliver repetitive mechanical nociceptive stimuli to the leeches as described in previous studies using rodents ( Cowie et al, 2018 ; Hogan et al, 2004 ), which has been shown to be a noxious/sensitizing stimuli in Hirudo ( Mack et al, 2022 ). Needle pokes were applied to the posterior sucker, which is easy to consistently target with repeated pokes in the same location ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A 25-gauge needle was used to deliver repetitive mechanical nociceptive stimuli to the leeches as described in previous studies using rodents ( Cowie et al, 2018 ; Hogan et al, 2004 ), which has been shown to be a noxious/sensitizing stimuli in Hirudo ( Mack et al, 2022 ). Needle pokes were applied to the posterior sucker, which is easy to consistently target with repeated pokes in the same location ( Fig.…”
Section: Methodsmentioning
confidence: 99%